Hubungan Pendampingan Suami Saat Proses Persalinan Terhadap Kecemasan Pada Ibu di Klinik Pratama MARS Kecamatan Pagar Merbau Tahun 2023 - Sidabukke, Ida Ria R; Ernawati Barus (Universitas Sari Mutiara Indonesia, 2023)
Labor or giving birth to a baby is a normal process for women of childbearing age. Childbirth is an important event that is eagerly awaited by every married couple, so all moral and material support is provided by the husband, family and even all members of society for the welfare of the mother and fetus. However, when approaching the birthing process, various feelings of anxiety occur for pregnant mothers, apart from being impatient to see their baby born into the world, fear and anxiety about facing the birthing process swirl in their minds. This study aims to determine the relationship between husband's assistance and anxiety during the birthing process at the Pratama Mars Clinic. This research uses an analytical research design with a cross-sectional approach. The research was conducted at the Pratama Mars Clinic, Pagar Merbau District. The sample in this study was all mothers giving birth in Oktober and Desember 2023 at the Pratama Mars Clinic, totaling 43 respondents, the sampling technique was accidental sampling. The results of the research show that there is a relationship between the husband's assistance during the birthing process and the mother's anxiety. with a p value (p=0.000). The need for husband's assistance during the birth process of his wife to provide encouragement and avoid the mother's anxiety during the birth process. Midwives should provide counseling to mothers during ANC to avoid anxiety during labor to make the delivery process smoother.